Influence of mind mapping method implementation on learning results social science is required from students interest - Astawa, Dewa Nyoman Wija (International research journal of management, IT and social sciences, 2019)
This study aimed at investigating the effect of the implementation of mind mapping learning method to the students’ social science achievement viewed from learning interest at the fourth-grade students of an elementary school in Denpasar city in the academic year 2016/2017. This study was quasi-experimental research which applied the posttest-only control group design involving 80 students of grade four at elementary school in Denpasar city who were selected by using the total sample sampling technique. The data of the students’ social science achievement and learning interest were collected and then analyzed using the Analysis of Covariance (Anacova). The result of this study showed that the students’ social science achievement who were treated with mind mapping learning method was higher compared to the students’ social science achievement of those treated with the conventional learning method. This difference was consistent even though the students’ learning interest has been controlled. Based on the result of this study, it is suggested that mind mapping learning method be applied in the teaching and learning process of social science at the elementary school.